CATATAN PERTAMA INFEKSI ANISAKID (NEMATODA) PADA IKAN KAKAP MERAH (Lutjanus malabaricus) DAN KERAPU (Epinephelus sexfasciatus) DI KABUPATEN GRESIK, INDONESIA - Muhammad Zainul Muttaqin; Anfa'u Mazida; Aminin Aminin (Jurnal Perikanan Pantura (JPP), 2021)
Anisakiasis is a human disease caused by infection of Anisakid (nematodes) from the Anisakidae family (genus: Anisakis, Pseudoterranova, and Contracaecum). Anisakid requires several hosts to complete its life cycle: paratenic host (crustacea, cephalopods, shellfish), intermediate host (fish) and a final host (marine mammals). However, humans can be infected by Anisakid by consuming the raw or undercooked host carrying the parasite. The aim of this study is to identify Anisakid in two species of marine fish; red snapper (Lutjanus malabaricus) and grouper (Epinephelus sexfasciatus) obtained from Gresik traditional markets. Anisakid identification was performed by characterization of morphological features using light microscopy. As the results, we found red snapper and grouper fish were infected by the larvae (L3) of Anisakis Type II with infection intensity and prevalence of 3.17 parasites/fish and 60%, 12.75 parasites/fish and 80%, respectively. This finding confirms the presence of Anisakid in fish for human consumption in the Gresik region and justifies further investigation.